Electroconvulsive therapy against the patients' will: A case series. (3rd April 2018) - Methfessel, Isabel; Sartorius, Alexander; Zilles, David
Abstract: Objectives: Electroconvulsive therapy (ECT) is the most effective therapy for severe depressive and psychotic disorders. As patients may be subject to legal incapacity and lack of insight, treatment may be administered against the patient's will. There is only limited evidence on the use of ECT against the patient's non-autonomous will. Methods: We report a series of eight patients who received ECT against their will in two German university medical hospitals between 2014 and 2016. The effectiveness, tolerability and patients' perspective are described. Results: Seven of eight patients were much or very much improved according to the Clinical Global Impression Scale. Capacity to consent was restored in seven patients. Transient side effects occurred in four patients. Seven patients agreed to receive further ECT in the treatment course. Conclusions: This case series suggests that ECT may (and sometimes should) be administered to severely ill, non-consenting patients against their will with good effectiveness. Potential and mostly moderate and transient side effects have to be weighed up against the potentially life-saving character of ECT in patients with, e.g., suicidality and food refusal. Most importantly, the patients' retrospective appraisal also justifies the administration of ECT in situations of severe mental illness and legal incapacity.